Validity Of A Paranoid Thoughts Due To Social Violence Scale In Juarez Mexico - Esparza Del Villar, Oscar Armando; Gutiérrez Vega, Marisela; Montañez Alvarado, Priscila; Carrillo Saucedo, Irene Concepción (European Scientific Journal, ESJ, 2016)
Paranoid thoughts related to social violence have been reported by people living in the city of Juarez, Mexico, due to the increase in social violence because of the war between drug cartels and the Mexican government. The Paranoid Thoughts Scale was developed to measure these thoughts and the present study analyzed the reliability and validity of the scale. The sample consisted of 173 participants with a mean age of 33.31 (s = 15.12) years, 65.7% females and 34.3% males. The exploratory factor analysis indicated a one factor scale with factor loadings ranging from 0.41 to 0.80 and an internal reliability of α = 0.85. The concurrent validity was analyzed by correlating the Paranoid Thoughts Scale with scales measuring anxiety (STAI and AMAS-C), stress (Stress Profile) and depression (PHQ- 9). All of the correlations were statistically significant and ranged from r = 0.21 to r = 0.36. The Paranoid Thoughts Scale is a valid scale that can be used to measure paranoid thoughts due to violence in people from Mexico.